2013
DOI: 10.1080/03601234.2013.778597
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal impact of paraquat on the life span and parasitic behavior ofDiaeretiella rapaeM’Intosh

Abstract: This study focuses on assessing the impact of sublethal doses of paraquat on the survival, the emergence, the life span and the parasitic behavior of Diaeretiella rapae M'Intosh (Hymenoptera: Braconidae). The impact of sublethal doses was measured at room temperature using different densities of the cabbage aphid Brevicoryne brassicae. The results reveal that the field dose of paraquat caused 100% mortality in D. rapae. The percentage emergence of D. rapae decreased from 80.5% in the control group to 71.5% whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In non-target insects, Cousins et al [9] reported the decreasing size of oenocytes of honeybee larvae after being exposed to very small concentrations of paraquat. Studies related to insect physiology also show that paraquat can decrease the number of the emergence of adult insects 3Bio Journal of Biological Science, Technology and Management 2(1): 1-6 Anggraeni et al and compromise the ovipositioning ability of a parasitoid wasp, Diaeretiella rapae [10]. More than 95% of herbicide use is exposed to water, plants and non-target organisms such as soil arthropods [11].…”
Section: Introductionmentioning
confidence: 99%
“…In non-target insects, Cousins et al [9] reported the decreasing size of oenocytes of honeybee larvae after being exposed to very small concentrations of paraquat. Studies related to insect physiology also show that paraquat can decrease the number of the emergence of adult insects 3Bio Journal of Biological Science, Technology and Management 2(1): 1-6 Anggraeni et al and compromise the ovipositioning ability of a parasitoid wasp, Diaeretiella rapae [10]. More than 95% of herbicide use is exposed to water, plants and non-target organisms such as soil arthropods [11].…”
Section: Introductionmentioning
confidence: 99%